Pengembangan Media Pembelajaran Augmented Reality Materi Sistem Tata Surya untuk Siswa Kelas V Sekolah Dasar - Azmi, Aldila Ulul; Alinda, Tasya; Ningtias, Legia Ayu; Putra, Zetra Hainul (Indonesian Journal of Science, Technology, Engineering, Art, and Mathematics Education, 2024)
Learning media is a tool used by teachers to convey information. As time goes by, learning media also develops. One effort to increase student learning motivation is to utilize Augmented Reality applications in developing learning media. In the current digital era, teachers are required to have high quality in order to become inspiring educators. The purpose of this research is to analyze the need for using Augmented Reality application technology for students, determine the design for developing science learning media on solar system material using Augmented Reality applications, and determine the effectiveness of science learning media based on Augmented Reality applications. The type of research used is Research and Development (R&D) with the development model used being the ADD development model using the ADDIE development model. Technological advances have enabled the introduction of technology-based learning media. The Augmented Reality application is a technology- based learning media that is safe for children. This application can be used as a medium for recognizing objects without having to bring the child to the object, simply by scanning the flashcard the object will look like it is real.